Effect of digital screen usage on the visual-vestibular system interaction - BAL, NİLÜFER (My University, 2023)
Background/aim This research aims to develop an original understanding of the subject by examining how digital screen usage correlates with visual-vestibular system interaction and the vestibuloocular refex mechanism using vestibular test parameters. Materials and methods The study included 59 healthy participants. Participants were divided into two groups according to their screen usage time 3–6 h (Group 1) and over 6 h (Group 2). Participants were asked questions about complaints after screen use. After that, Video Head Impulse, Dynamic Visual Acuity, Videonystagmography test was applied to the participants. Results DVA was signifcantly poor in group 2. In vHIT and Videonystagmography test, a signifcant diference was not observed between the groups. Conclusion There is no conclusive evidence that digital screen usage directly afects the peripheral or central vestibular systems. However, the decrease in DVA in individuals who use digital screens for more than 6 h may be related to the efects of digital screen exposure on the visual-vestibular system. Keywords Computer vision syndrome, Digital screen, Dynamic visual acuity, Visual-vestibular interaction, Oculomotor system
Keywords: Computer vision syndrome; Digital screen; Dynamic visual acuity; Visual-vestibular interaction; Oculomotor system